THE ROLE OF EDUCATION AND INVESTMENT IN EDUCATION ON THE LABOR MARKET INSERTION OF RECENT GRADUATES - ALINA SOMITCA, ELENA HLACIUC (USV Annals of Economics and Public Administration)
The issue of the insertion of graduates into the labor market remains a priority for decision-makers in international higher education. These concerns have received increased attention in the current climate of uncertainty in the labor market. Policymakers continue to emphasize the importance of 'employability skills' so that graduates are fully prepared to meet the challenges of the ever-changing labor market. This paper reviews some of the key empirical and conceptual themes in the field of labor market placement of higher education graduates over the last decade and attempts to demonstrate the role of educational attainment and investment in education on labor market placement. With the help of econometric modelling, we tried to highlight the influence on the insertion on the labor market of the level of graduated studies, the financing given to education and public investments in the education system.